Micellar Electrokinetic Capillary Method for the Analysis of Rivaroxaban and its Correlation with RP–LC Method and Bioassay - Elesbao Walter, Mauricio; Ferreira Perobelli, Rafaela; Gustavo Jung Motta, Luis; Rosa da Silveira, Alice; Xavier, Bruna; LuizDalmora, Sergio (Current Analytical Chemistry, 2017)
Background: Rivaroxaban is clinically indicated for the prophylaxis and treatment of thromboembolic diseases. A stability-indicating micellar electrokinetic capillary chromatography (MEKC) method was validated for the analysis of rivaroxaban (RIV), using linezolid as an internal standard (IS), showing the capability to resolve from its potential impurities and degradation products, which is highly recommended for the quantitative analysis of pharmaceutical formulations. Methods: The background electrolyte solution consisted of 75 mM MES buffer and 25 mM sodium dodecyl sulphate (SDS) solution at pH 2. Injections were carried out using a pressure mode at 50 mbar for 60 s, with detection by a photodiode array detector set at 202 nm. Results: Specificity and stability-indicating capability of the method were established in degradation studies, which also showed that there was no interference of the excipients. The method was linear over the concentration range of 0.5 – 50 μg mL-1 (r2 = 0.9991) and the detection limit (DL) and quantitation limit (QL) were 0.16 μg mL-1 and 0.54 μg mL-1, respectively. The accuracy was 100.67% with bias lower than 1.60%. Conclusion: The proposed method was applied to the quantitative analysis of RIV in tablet dosage forms and the results were correlated to those of the validated reversed-phase liquid chromatography (RP-LC) and the anti-factor Xa assay, with non-significant differences (p > 0.05), contributing to evaluate an alternative to improve quality control, and to assure therapeutic efficacy of the pharmaceutical product.
Keywords: Micellar electrokinetic capillary chromatography